Indoor propagation model for office environment at 900 MHZ and 1800 MHZ - Erol, Mehmet Akif. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
Propagation of electromagnetic waves became an important area of research since the invention of wireless communication. Propagation models are generally divided into three categories. First category includes terrestrial and satellite link communication channel. This propagation environment is characterized by very long range, atmospheric e ects and generally LOS propagation. Second category includes macrocells which are generally regarded as primary communication hubs of GSM network. Macrocell propagation environment is associated with street canyons, tall buildings, hills and trees. Third and last category includes picocells which are base stations located inside buildings. Indoor propagation environment presented new challenges such as multiwall penetration, di raction through corners and re ection from the walls. During the last decade, the necessity of using the same bandwidth for as many custormers as possible began to force GSM providers to deploy more and more picocells into indoor environments. This development increased the importance of precise and easy-to-use propagation models. Several empirical and theoretical propagation models for indoor propagation were proposed by various researchers. However, unlike macrocell models, none of those models seem to be de facto norm for quick propagation assesment and they generally produce varying results. In this dissertation, existing indoor propagation models were applied to a typical o ce building environment at two main GSM frequencies, comparison and accuracy of di erent models were presented and nally an optimized model adjusted speci cally to an o ce environment was proposed using previous work as a base.
Keywords: Wireless communication systems.; Local area networks (Computer networks)